1998
DOI: 10.1007/s000110050355
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of myricetin-3-O-β-D-glucuronide and related compounds

Abstract: MGL is a COX-1, COX-2 and 5-LOX inhibitor. In view of the moderate in vitro activity and the very potent in vivo activity an additive mechanism must be involved. Small changes in the molecular structure lead to the loss or reduction of the anti-inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Thus, the own biological activity of the glucuronides should be considered, even though the possibility of hydrolysis into aglycones inside the cells is still under investigation (O'Leary et al, 2001;Shimoi et al, 2001). A few studies have reported antioxidative or anti-inflammatory activity of flavonoid conjugates (Manach et al, 1998;Hiermann et al, 1998;Day et al, 2000;Moon et al, 2001). The intestinal microflora, besides the deglycosylation of narirutin and hesperidin, has also the capacity to degrade the aglycones into phenolic acids such as p-hydroxyphenylpropionic, p-coumaric, and p-hydroxybenzoic acids (Booth et al, 1958;Scheline, 1991;Felgines et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the own biological activity of the glucuronides should be considered, even though the possibility of hydrolysis into aglycones inside the cells is still under investigation (O'Leary et al, 2001;Shimoi et al, 2001). A few studies have reported antioxidative or anti-inflammatory activity of flavonoid conjugates (Manach et al, 1998;Hiermann et al, 1998;Day et al, 2000;Moon et al, 2001). The intestinal microflora, besides the deglycosylation of narirutin and hesperidin, has also the capacity to degrade the aglycones into phenolic acids such as p-hydroxyphenylpropionic, p-coumaric, and p-hydroxybenzoic acids (Booth et al, 1958;Scheline, 1991;Felgines et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The highly anti-inflammatory compound 2 (Hiermann et al, 1991(Hiermann et al, , 1998 was present only in minor quantities (0.1-0.3 mg/g) with significant lower amounts at 800 m compared with 1000 and 1500 m.…”
Section: Quantification Of Individual Flavonoidsmentioning
confidence: 97%
“…Rosebay willow-herb shows antioxidative, anti-inflammatory, antimicrobial, antiproliferative, and anti-exudative activities (Hevesi Toth et al, 2009;Kiss et al, 2011;Kosalec et al, 2013;Onar et al, 2012;Stolarczyk et al, 2013b;Vitalone et al, 2001Vitalone et al, , 2003Vogl et al, 2013). The anti-inflammatory activity of E. angustifolium has been closely related to its flavonoids evidenced by the finding of myricetin 3-O-glucuronide as strongly active (4 10-fold more potent than indomethacin) in the rat paw edema test, a model of acute inflammation (Hiermann et al, 1998) and showing an inhibitory effect on prostaglandin biosynthesis (Hiermann et al, 1991). However, for treatment of benign prostate hyperplasia, tannins also seem to play a role as 5a-reductase and aromatase were inhibited by the tannins oenotheins A and B.…”
Section: Introductionmentioning
confidence: 99%
“…Besides anticancer, antiviral, antimicrobial, immunmodulatory and antithrombotic activities, the anti-inflammatory properties, observed in vitro and in vivo, are most recognized. Thus, flavonoids have been shown to inhibit acute or chronic inflammation in various animal models such as rat Freund's adjuvant arthritis [98], [99] and carrageenan-induced mouse paw edema, when given orally [99], [100]. In particular, however, flavonoids showed beneficial effects in AA-induced ear edema, when applied topically (for review see [97]).…”
Section: Inhibitors Of 5-lo Product Synthesis From Plant Originmentioning
confidence: 99%
“…Unfortunately, among those, only for papyriflavonol 20 has the efficacy in intact cells been demonstrated [103]. Although for inhibition of cellular 5-LO, the flavonoid aglycones are generally superior over the corresponding glycosides, the myricetin 3-O-b-D-glucuronide 13 is more efficient than the corresponding aglycone myricetin 12 under comparable assay conditions [99], [109], probably related to more effective cellular uptake of the glycoside by specific transporters. Since conventional flavonoids show only weak efficacy after oral administration, presumably due to poor bioavailability (low absorption) and/or rapid metabolism and elimination, the more lipophilic prenylated derivatives may possess the advantage of facilitated membrane (and skin) penetration in addition to their higher potency as 5-LO inhibitors, suggesting a potential for topical treatment of inflammatory skin diseases [103], [105], [113].…”
Section: Inhibitors Of 5-lo Product Synthesis From Plant Originmentioning
confidence: 99%